2013
DOI: 10.1002/bapi.201310077
|View full text |Cite
|
Sign up to set email alerts
|

Die Entwicklung eines mineralischen Feuchtespeicher‐Grundputzes

Abstract: Im folgenden Aufsatz wird die Entwicklung eines Feuchtespeicherputzes auf mineralischer Basis beschrieben. Im Rahmen eines schweizerischen Forschungsprojekts zur Restaurierung von historischen Gebäuden wurden unterschiedliche, als feuchtespeichernd bekannte Putze nach dem Nordtestverfahren untersucht. Durch die anschließende Neuentwicklung konnte gezeigt werden, dass sich der optimierte Feuchtespeicherputz von heutigen, marktgängigen Produkten durch eine bis zu 9‐fache Feuchteaufnahme auszeichnet. Die Forschun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Consequently, gypsum cannot be compared with these studies. Lime plaster performances are in line with Tittarelli et al [41] and Stahl et al [5] results, in which lime mixed with sand has the worst MBV performances (0.50-0.88 g/(m 2 • %RH)).…”
Section: Materials Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…Consequently, gypsum cannot be compared with these studies. Lime plaster performances are in line with Tittarelli et al [41] and Stahl et al [5] results, in which lime mixed with sand has the worst MBV performances (0.50-0.88 g/(m 2 • %RH)).…”
Section: Materials Propertiessupporting
confidence: 87%
“…The laboratory test showed clay and gypsum plaster exchange more humidity than lime, while other studies showed similar moisture buffering values for clay [3,5,39], but gypsum presented in general moisture buffering values lower than 0.95 g/(m 2 •%RH). However, the moisture buffering results for gypsum presented by Stahl et al [5] and Santos et. al.…”
Section: Materials Propertiesmentioning
confidence: 57%
See 1 more Smart Citation
“…A study by Stahl et al (2013) investigated the improvement of the buffering capacity of plasters. Two clay plasters were included as reference in the study ('Lehmputz 1' and 'Lehmputzt 2'); following the Nordtest procedure the plasters were measured and showed moisture adsorption at 8 h of 59 and 53 g/m 2 .…”
Section: Improving the Adsorption Capacitymentioning
confidence: 99%
“…Some materials, described as hygroscopic, have the ability to passively control the indoor climate, reducing operational energy. Timber [7], clay [8] and other novel materials, such as zeolite [9] and mineral based plasters [10] reduce the peaks and valleys of internal Relative Humidity, due to their ability to adsorb and desorb moisture, a process referred to as moisture buffering [11].…”
Section: Introductionmentioning
confidence: 99%